Successful Accreditation Techniques - Baker, Shirley; Camden-Anders, Sherry (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2020)
AbstractThe challenges of accreditation reviews create a sense of stress across academic institutions that can be significantly reduced when strategies are implemented and maintained. Understanding the purpose, value, and benefits of the accreditation process is critical. Two techniques that lead to accreditation success include ongoing program meetings resulting in assigned tasks that address government or commission evaluation standards, and the use of a program matrix. The article includes meeting strategies and a universally adaptable matrix design. Moving from stress to success is possible when the techniques are linked to all standards and subsections, and each task successfully meets accreditation requirements.AbstrakTantangan akreditasi menciptakan rasa stres di seluruh institusi akademik, hal ini dapat dikurangi, secara signifikan ketika strategi diterapkan dan dipertahankan. Memahami tujuan, nilai, dan manfaat dari proses akreditasi sangatlah penting. Dua teknik yang mengarah pada keberhasilan akreditasi, termasuk program rapat yang sedang berjalan sehingga menghasilkan tugas-tugas saat membahas standar evaluasi pemerintah atau komisi, dan penggunaan matriks program. Artikel ini mencakup strategi rapat dan desain matriks yang dapat disesuaikan secara universal. Beralih dari rasa stres akan keberhasilan akreditasi, hal ini memungkinkan jika teknik ini dikaitkan dengan semua standar dan subbagian, serta setiap tugas yang berhasil memenuhi persyaratan akreditasi.How to Cite: Baker, S., Camden-Anders, S. (2020). Successful Accreditation Techniques. TARBIYA: Journal of Education in Muslim Society, 7(2), 226-240. doi:10.15408/tjems.v7i2. 20592.